Strengthening Counselor Competencies in the Independent Learning Era through Training on Non-Cognitive Diagnostic Assessment Development - Widya Multisari; Arbin Janu Setiyowati; Khairul Barriyah; Riskiyana Prihatiningsih; Hengki Tri Hidayatullah; Anwar Luthfi (Jurnal Pengabdian Masyarakat, 2023)
Purpose: The need for diagnostic assessment in the independent curriculum necessitates school counselors to be able to provide valid and reliable instruments to assess students' conditions. One crucial aspect to consider is the psychological well-being of students. Therefore, training in developing non-cognitive diagnostic assessments is necessary to support counselor competencies in the era of independent learning curriculum. Method: The training utilized the ADDIE training model, starting from analysis, design, development, implementation, and evaluation. This model was employed to assist in implementing training tailored to the participant's needs. The evaluation was conducted through process evaluation and outcome evaluation. Practical Applications: The training resulted in the development of a psychological well-being scale by school counselors. Subsequently, the scale underwent construct validation by experts, as well as validity and reliability testing using SPSS 24. A guide for using the psychological well-being scale was then created, including rationale, usage instructions, interpretation guidelines, and sample assessment result presentations. Conclusion: The training successfully enhanced counselor competencies in developing non-cognitive diagnostic assessments.